2014
DOI: 10.1155/2014/629507
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3βInhibition Attenuates CLP-Induced Liver Injury by Reducing Inflammation and Hepatic Cell Apoptosis

Abstract: Liver dysfunction has been known to occur frequently in cases of sepsis. Excessive inflammation and apoptosis are pathological features of acute liver failure. Recent studies suggest that activation of glycogen synthase kinase- (GSK-) 3β is involved in inflammation and apoptosis. We aimed to investigate the protective effects of GSK-3β inhibition on polymicrobial sepsis-induced liver injury and to explore the possible mechanisms. Polymicrobial sepsis was induced by cecal ligation and puncture (CLP), and SB2167… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Evidence indicates that inflammatory cytokines play an important role in sepsis; pro-inflammatory cytokines and anti-inflammatory cytokines counteract each other and reach an immunological equilibrium, which leads to various types of tissue damage and organ injury (8). In the present study, elevated TNF-α, IL-6 and IL-10 levels were observed in the livers of rats in the CLP group in comparison with those in the control group, which is consistent with previous studies (27,28). Moreover, Xuebijing injection has been found to reduce the secretion of TNF-α and IL-6 by Kupffer cells in livers of rats with heart stroke (29), and promote IL-10 expression in rabbits with oleic acid-induced acute lung injury (30).…”
Section: Discussionsupporting
confidence: 92%
“…Evidence indicates that inflammatory cytokines play an important role in sepsis; pro-inflammatory cytokines and anti-inflammatory cytokines counteract each other and reach an immunological equilibrium, which leads to various types of tissue damage and organ injury (8). In the present study, elevated TNF-α, IL-6 and IL-10 levels were observed in the livers of rats in the CLP group in comparison with those in the control group, which is consistent with previous studies (27,28). Moreover, Xuebijing injection has been found to reduce the secretion of TNF-α and IL-6 by Kupffer cells in livers of rats with heart stroke (29), and promote IL-10 expression in rabbits with oleic acid-induced acute lung injury (30).…”
Section: Discussionsupporting
confidence: 92%
“…This kinase is an upstream activator Akt (PKB) and this in turn inhibits the GSK-3␤ activity via phosphorylation of ser9, allowing glycogen synthase to be dephosphorylated and glycogen synthesis to be started [28]. Inactivation of GSK-3␤ by the PI3K/Akt signaling pathway also participate in the regulation of inflammatory pathways, as it has been shown that Akt induced inhibition of GSK-3␤ negatively modulate the NF-B pathway [29]. Moreover, it has been demonstrated that GSK-3 inhibits production of pro-inflammatory cytokines (like IL-␤, IL-6 and IFN-␥) and increases release of antiinflammatory cytokines (like IL-10) [30].…”
Section: Gsk-3␤ and Inflammatory Mechanismmentioning
confidence: 99%
“…A growing number of studies demonstrate a pathogenic role for GSK3␤ in end-organ damage in murine models of sepsis. Liver injury has been shown to be mediated by GSK3␤ activity and hepatocellular injury decreases with the use of GSK3␤ inhibitors (26,27). More recently, murine models of ARDS demonstrate an active role of GSK3␤ in mediating acute lung inflammation and alveolar damage (28,29).…”
mentioning
confidence: 99%